Exploring Segregation and Sharing in Belfast: A PGIS Approach. Issue 1 (2nd January 2019) - Huck, Jonny J.; Whyatt, J. Duncan; Dixon, John; Sturgeon, Brendan; Hocking, Bree; Davies, Gemma; Jarman, Neil; Bryan, Dominic
Abstract : This article presents a novel exploratory investigation into the location and characteristics of spaces that are segregated and shared between Protestant and Catholic communities in Belfast, Northern Ireland (UK). Focusing on a particularly segregated part of the city, this study uses state-of-the-art participatory geographic information systems (PGIS) and visualization techniques to create qualitative, bottom-up maps of segregation and sharing within the city, as experienced by the people who live there. In doing so, it identifies important and previously unreported patterns in segregation and sharing between sectarian communities, challenging normative approaches to PGIS and illustrating how alternative methods might provide deeper insights into complex social geographies such as those of segregation. Finally, the findings of this work are formulated into a set of hypotheses that can contribute to a future research agenda into segregation and sharing, both in Belfast and in other divided cities. Key Words: nonplace, PGIS, segregation, visualization. 本文对北爱尔兰（英国）贝尔法斯特的新教与天主教社群之间隔离与分享的空间区位及特徵, 提出崭新的解释性探讨。本研究聚焦该城市中特别受到隔离的部分, 运用最先进的参与式地理信息系统 (PGIS)以及可视化技术, 创造质化、由下而上的当地居民感受到的城市隔离和分享地图。本研究藉由这麽做, 指认出重要且过往未受到报导的教派社群间的隔离与分享模式, 挑战 PGIS 的规范性方法, 并阐明另类方法如何可能对诸如隔离等复杂的社会地理提出更为深刻的洞见。最后, 本研究的发现将形成一组假说, 对于有关在贝尔法斯特与其他分裂城市中的隔离与分享之未来研究议程作出贡献。 关键词：非地方, 参与式地理信息系统 (PGIS), 隔离, 可视化。 Este artículo presenta una nueva investigación exploratoria sobre la localización y características de espacios segregados y compartidos entre las comunidades protestantes y católicas de Belfast, Irlanda del Norte (RU). Enfocándose sobre una parte particularmente segregada de la ciudad, este estudio usa sistemas de información geográfica participativos (PSIG) de última generación y técnicas de visualización para crear mapas cualitativos ascendentes de segregación y participación dentro de la ciudad, tal como lo experimenta la gente que reside allí. Al hacerlo, se identifican importantes patrones de segregación y participación entre comunidades sectarias previamente inadvertidos, retando a los PSIG los enfoques normativos e ilustrando el modo como métodos alternativos podrían producir un entendimiento más profundo en las complejas geografías sociales, tales como las de la segregación. Por último, los hallazgos de este trabajo se formulan en un conjunto de hipótesis que pueden contribuir en una futura agenda de investigación de segregación y participación, tanto en Belfast como en otras ciudades divididas